Acetaminophen as a renoprotective adjunctive treatment in patients with severe and moderately severe falciparum malaria : a randomized, controlled, open-label trial - Charunwatthana, Prakaykaew (2019)
Background: Acute kidney injury independently predicts mortality in falciparum malaria. It is unknown whether acetaminophen’s capacity to inhibit plasma hemoglobin-mediated oxidation is renoprotective in severe malaria. Methods: This phase 2, open-label, randomized controlled trial conducted at two hospitals in Bangladesh assessed effects on renal function, safety, pharmacokinetic (PK) properties and pharmacodynamic (PD) effects of acetaminophen. Febrile patients (>12 years) with severe falciparum malaria were randomly assigned to receive acetaminophen (1 g 6–hourly for 72 hours) or no acetaminophen, in addition to intravenous artesunate. Primary outcome was the proportional change in creatinine after 72 hours stratified by median plasma hemoglobin. Results: Between 2012 and 2014, 62 patients were randomly assigned to receive acetaminophen (n = 31) or no acetaminophen (n = 31). Median (interquartile range) reduction in creatinine after 72 hours was 23% (37% to 18%) in patients assigned to acetaminophen, versus 14% (29% to 0%) in patients assigned to no acetaminophen (P = .043). This difference in reduction was 37% (48% to 22%) versus 14% (30% to −71%) in patients with hemoglobin ≥45000 ng/mL (P = .010). The proportion with progressing kidney injury was higher among controls (subdistribution hazard ratio, 3.0; 95% confidence interval, 1.1 to 8.5; P = .034). PK–PD analyses showed that higher exposure to acetaminophen increased the probability of creatinine improvement. No patient fulfilled Hy’s law for hepatotoxicity. Conclusions: In this proof-of-principle study, acetaminophen showed renoprotection without evidence of safety concerns in patients with severe falciparum malaria, particularly in those with prominent intravascular hemolysis.